Is Janssen responsible for the shock? - Maharjan, Kripa; Tiwary, Abhishek (Journal of General Practice and Emergency Medicine of Nepal, 2021)
A 53-year-old male with no known comorbidities presented in emergency department of Trishuli Hospital in shock with 3 days’ history of swelling of whole body and 1-day history of difficulty breathing 3 days after receiving the Janssen Ad26.COV2.S vaccine. Nepal on 19th July, 2021 started the inoculation campaign of Johnson and Johnson vaccine, the third COVID-19 shot approved for public use in the country. Twenty-eight cases of cerebral venous sinus thrombi were reported after receiving the Janssen Ad26.COV2.S vaccine, out of which three cases expired.3 However, no cases of shock post vaccine has been reported till date. The cause of shock in this patient was not clear. The patient could have massive pulmonary embolism leading to shock with the fact that no other septic foci was found in this patient. As there has been rising demand of the vaccine and unmet need, the general public are going to extreme extent. There should be robust public health awareness and follow up post vaccination. The government and health organizations should be focusing more on the post vaccination status of the public, so that we can prevent such adverse events in future.